Infections in gynecology and obstetrics. Microbiology of the female genital tract. - Gonzales Enders, Rodolfo (2015)
Over the years it has shown that a variety of microorganisms colonize certain tissues, such as skin, mouth, gastrointestinal tract and vagina, but even though they are closely related to the host will not cause disease; these organisms should be called "normal", a term which is currently not acceptable. It is more appropriate to call them "prevalent" or "native" because apparently harmless species with pathogenic and beneficial are still some there intermingle.